Peran Keterampilan Menyimak dalam Pembelajaran Sains Interaktif pada Materi Biotik, Abiotik, dan Tata Surya di SDI Wolowaru 5: Pengabdian - Bs, Yohana Nono; We’u, Gregorius; Rae, Klarita Selvina; Gijung, Adelia Jen; Ndui, Elin Febriana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This activity was carried out by students of the Elementary School Teacher Education Study Program at the University of Flores using a descriptive qualitative approach. Data were collected through observation and documentation during the learning process. The purpose of this activity was to improve students’ listening skills in interactive science learning on the topics of Biotic, Abiotic, and the Solar System. The results showed that listening skills play an important role in helping students understand scientific concepts more deeply. Students with good listening skills were able to capture information accurately, respond correctly to teachers’ questions, and relate the material to their everyday experiences. The use of interactive learning strategies such as group discussions, visual media, learning videos, and educational games was proven to increase students’ interest, attention, and active participation during the learning process. Therefore, listening skills are a key factor supporting the effectiveness of science learning in elementary schools and should be continuously developed through creative, innovative, and enjoyable teaching methods